Politicians doing business: Evidence from Mozambique - Sam Jones; Felix Schilling; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
We link a new database of politically exposed persons with the complete register of firms established in Mozambique since Independence. Focusing on the network of connections between firm owners, we use a generalized event study analysis to show that holders of political office achieve significant gains in the number of companies owned and their structural power (centrality) within the business-owner network. These gains are concentrated in joint-stock firms active in provision of business services, and our results persist when we aggregate the data to the family-level. This pattern suggests politicians accumulate private sector wealth by acting as rentier-brokers.
Keywords: D72; G30; G38; 330; firm registry; beneficial ownership; political connections; rent-seeking; Mozambique